Clinical significance of cancerous inhibitor of protein phosphatase 2A in human cancers - Anchit Khanna; John E. Pimanda (2015)
Cancerous Inhibitor of Protein Phosphatase 2A (CIP2A), a recently identified oncogene, has emerged as a potential drug target for a range of different tumor types. High CIP2A expression has been reported in almost all solid organ cancers and in some hematological tumors and is associated with high grade and poor prognosis. Notably, high CIP2A expression is determined in over 70% of tumor patient samples in the majority of human cancers. High expression of CIP2A has also been proposed as a useful biomarker that predicts therapeutic response to chemotherapeutics such as Bortezomib, Erlotinib, Checkpoint Kinase 1 inhibitors and pro-senescence based therapies. In this review, we highlight, critically evaluate and discuss the ambiguity in CIP2A's prognostic role in different human cancers and its role in modulating response and resistance to chemotherapeutics.